Cathepsin G activity as a new marker for detecting airway inflammation by microscopy and flow cytometry - Guerra, Matteo; Frey, Dario; Hagner, Matthias; Dittrich, A. Susanne; Paulsen, Michelle; Mall, Marcus A.; Schultz, Carsten (ACS central science, 2019)
Muco-obstructive lung diseases feature extensive bronchiectasis due to the uncontrolled release of neutrophil serine proteases into the airways. To assess if cathepsin G (CG) is a novel key player in chronic lung inflammation, we developed membrane-bound (mSAM) and soluble (sSAM) FRET reporters. The probes quantitatively revealed elevated CG activity in samples from 46 patients. For future basic science and personalized clinical applications, we developed a rapid, highly informative, and easily translatable small-molecule FRET flow cytometry assay for monitoring protease activity including cathepsin G. We demonstrated that mSAM distinguished healthy from patient cells by FRET-based flow cytometry with excellent correlation to confocal microscopy data.